2015
DOI: 10.1159/000441012
|View full text |Cite
|
Sign up to set email alerts
|

Presence and Number of Positive Surgical Margins after Radical Prostatectomy for Prostate Cancer: Effect on Oncological Outcome in a Population-Based Cohort

Abstract: Introduction: Additional insight in the occurrence and number of positive surgical margins (PSM) and the potential consequences is needed, since earlier studies show divergent results. This study aims at investigating the effect of the presence and number of PSM on oncological outcomes. Methods: Retrospective population-based cohort study including 648 consecutive prostate cancer patients who underwent RP in the Southern Netherlands in 2006-2008. The effect of PSM on risk of treatment failure, defined by eithe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 20 publications
1
6
1
Order By: Relevance
“…Indeed, in recent years, mpMRI of the prostate has shown to be an effective tool for identifying areas of suspicion that correlate with cancer upgrading and upstaging [22,23,24]. Moreover, it has recently been shown that mpMRI is an effective tool for both local staging and planning nerve-sparing surgery in patients undergoing RP [25,26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…Indeed, in recent years, mpMRI of the prostate has shown to be an effective tool for identifying areas of suspicion that correlate with cancer upgrading and upstaging [22,23,24]. Moreover, it has recently been shown that mpMRI is an effective tool for both local staging and planning nerve-sparing surgery in patients undergoing RP [25,26,27]. …”
Section: Discussionmentioning
confidence: 99%
“…All 30 studies were retrospective in design, the time of publication ranged from 2006 to 2023, and the mean follow-up durations varied from 1.5 to 13 years. Among the studies, nine [9,12-19] , six [17,20-24] , 14 [12,17,20,23-33] and, 13 [23,26-28,30,33-40] studies evaluated the relationships between PGG, PSM length, number of PSMs, pathologic stage of the tumor, and BCR, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…14 [12,17,20,[23][24][25][26][27][28][29][30][31][32][33] and, 13 [23,[26][27][28]30,[33][34][35][36][37][38][39][40] studies evaluated the relationships between PGG, PSM length, number of PSMs, pathologic stage of the tumor, and BCR, respectively.…”
Section: Study Characteristics and Quality Assessmentsmentioning
confidence: 99%
“…Second, our correct system was based on several ready predictors. Some novel biomarkers and factors such as IL6, TGFβ and positive surgical margins [24,25] were not included in the new correct system because of health care restrictions in China. Third, we have not tested the performance of the correct system in an external dataset.…”
Section: Discussionmentioning
confidence: 99%